Development of A Nursing Care Documentation Module Based on SDKI, SLKI, SIKI (3S) - Emi Eliya Astutik; M. Elyas Arif Budiman; Achmad Efrizal Amrullah; Mahmud Ady Yuwanto (Babali Nursing Research)
Backgroud: Nursing documentation is an important aspect of the nursing care workflow. Ineffective nursing documentation practices have been reported to negatively impact patient outcomes and health worker efficiency. Providing training for nurses will create positive attitudes and improve nurses' knowledge of nursing documentation. The purpose of this study was to determine the effectiveness of documentation training based on SDKI, SLKI and SIKI (3S) on the the quality of documentation of independent practice nurses.